The Correlation between Studentsâ Learning Strategy and Studentsâ English Achievement to the Eighth Grade Students of SMPN H. Wukirsari. - Triyogo, Agus; Syaprizal, Syaprizal; Hardiyanto, Hardiyanto (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2018)
This study tried to investigate the correlation between studentsâ learning strategy and studentsâ English achievement to the eighth-grade students of SMPN H. Wukirsari. There were two problems which discussed in this study. First was there any correlation between studentsâ learning strategy and studentsâ English achievement to the eighth-grade students of SMPN H. Wukirsari? Second, what was the percentage of Studentsâ Learning Strategy? The objectives of this study were to find out the percentages of studentsâ learning strategy and to find out the correlation between studentsâ learning strategy and studentsâ English achievement to the eighth-grade students of SMPN H. Wukirsai. The method used in this study was correlation research. The population of this study was all of the eighth-grade students of SMPN H. Wukirsari in the academic year 2015/2016.Â  The total number of population was 182 students which were distributed into six classes. There were 28 students treated as the sample of the study. The sample was taken through random sampling. In collecting the data of studentsâ learning strategy, the writer used questionnaire by strategy inventory for language learning and in collecting the data of studentsâ English achievement, the writer used studentsâ report score. Then, the technique for analyzing the data, the writer used Spearman Rank Correlation to find out the correlation between studentsâ learning strategy and studentsâ English achievement. Based on the findings, the result of the calculation correlation between studentsâ learning strategy and studentsâ English achievement was 0.542, whereas the coefficient of correlation was 0.318 (robtained > rtable ). So the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected, it means that there was a correlation between studentsâ learning strategy and studentsâ English achievement to the eighth-grade students of SMPN H. Wuirsari in the academic year of 2015/2016. Finally, the aim of this article was to clarify on studentsâ learning strategy and studentsâ English achievement.